2012
DOI: 10.1177/0961203312437270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxychloroquine treatment on pro-inflammatory cytokines and disease activity in SLE patients: data from LUMINA (LXXV), a multiethnic US cohort

Abstract: Objective We sought to determine the effect of hydroxychloroquine therapy on the levels proinflammatory/prothrombotic markers and disease activity scores in patients with systemic lupus erythematosus (SLE) in a multiethnic, multi-center cohort (LUMINA). Methods Plasma/serum samples from SLE patients (n=35) were evaluated at baseline and after hydroxychloroquine treatment. Disease activity was assessed using SLAM-R scores. Interferon (IFN)-α2, interleukin (IL)-1β, IL-6, IL-8, inducible protein (IP)-10, monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(145 citation statements)
references
References 43 publications
8
121
2
6
Order By: Relevance
“…Shown are the representative results of three separate experiments with similar results. A B mokines promote the formation and development of atherosclerotic plaque as well as intravascular thrombi in patients with autoimmune diseases [35][36][37][38][39][40][41] . Although the involvement of cytokines and chemokines in the pathogenesis of atherosclerosis and autoimmune diseases is widely accepted, little is known about the underlying mechanisms or how these molecules trigger vascular inflammation and interact with autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Shown are the representative results of three separate experiments with similar results. A B mokines promote the formation and development of atherosclerotic plaque as well as intravascular thrombi in patients with autoimmune diseases [35][36][37][38][39][40][41] . Although the involvement of cytokines and chemokines in the pathogenesis of atherosclerosis and autoimmune diseases is widely accepted, little is known about the underlying mechanisms or how these molecules trigger vascular inflammation and interact with autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hydroxychloroquine blocks TLR-mediated activation of pDC in vitro, as shown by inhibition of IFNa synthesis, either after induction by immune-complexes [9] or upon stimulation with TLR9 agonists [48,49]. Recently, it has been observed that the significant clinical improvement in SLE patients after hydroxychloroquine therapy correlated with reductions in IFNa levels [50]. Furthermore, treatment with hydroxychloroquine was associated with an impaired ability of pDCs from subjects with SLE to produce IFNa and TNFa upon stimulation with TLR7/9 agonists [51].…”
Section: Discussionmentioning
confidence: 99%
“…Терапия статинами в исследовании LUMINA (LXXVI) привела к существенному уменьшению индекса активности SLAM-R и значительному клиническому улучшению у пациентов с СКВ [89]. На модели СКВ у мышей NZB/W F1 лечение аторвастатином уменьшило уровень антител к нативной ДНК [90].…”
Section: о б з о р ыunclassified